Analysis of Fingerprint (E-Ticket) Product Innovation on The Number of Sales in CV. Dinamika Karya Cirebon - Prahitaningtyas, Sherina; Azzahra, Adelia; Oktavia, Silvi (Ridwan Institute, 2023)
This research aims to assess the influence of product innovation on sales performance at CV. Dynamics of Cirebon Works. The study proposes two variables: product innovation as an independent variable and the number of sales as a dependent variable. Product innovation is defined as the process or outcome of enhancing the utility of an existing product and adding more meaningful value. Some sources also suggest that product innovation involves updating various products to provide greater benefits to consumers. The research methodology employed descriptive survey methods, utilizing interviews and questionnaires distributed to employees at CV. Dynamics of Cirebon Works for sampling. Hypothesis testing was conducted to establish the connection between product innovation and sales using the product-moment correlation, t-test formulas, determination coefficients, and simple regression analysis. The findings indicate a positive impact of product innovation, as evidenced by the strong agreement of 39.02%, agreement of 12.19%, hesitation of 9.75%, disagreement of 19.5%, and strongly disagreeing at 2.43%. Additionally, sales data processing reveals a positive trend, with a strong agreement of 79.4%, hesitation at 14.70%, and disagreement at 11.76%. Statistical analysis yielded a correlation coefficient of 0.697, indicating a robust correlation. The t-test resulted in a t-value of 4.655 with degrees of freedom (df) of 32 (34 – 2), and a critical t-value (t-table) of 3.942 at a significance level of 5%. Given that thitung>ttable (4.655>3.942), the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This signifies a positive influence between product innovation and the number of sales. Consequently, the study concludes that product innovation significantly contributes to increased sales at CV. Dynamics of Cirebon Works.